Evaluating shifting perceptions and configurations of social capital in leadership development. (February 2023) - Gilani, Parisa; Bolden, Richard; Pye, Annie
Whilst Day's (2000) description of leadership development as an investment in social capital has been widely cited, there has been little subsequent empirical or theoretical work to explore and articulate the nature and purpose of this 'social capital' or how it changes over time. This paper revisits this issue by presenting findings from a qualitative in-depth longitudinal evaluation of a corporate leadership development programme. The study explored the multi-faceted and shifting nature of social capital during and after the programme, with particular attention given to how different aspects of social capital were perceived and engaged with by key stakeholders over time. Findings reveal differing perspectives on the nature and purpose of social capital and illustrate the impact of changing organizational contexts on programme aims and outcomes and how these are evaluated. The paper concludes by outlining implications for the evaluation of leadership development, advocating the value of a pluralistic approach that incorporates criticality alongside the logics of accountability, development and knowledge that characterise most current approaches to evaluationKennedy, Carroll and Francoeur (2013) .